Live Streaming Sales, Trust, Content Marketing Tiktok Application and Consumer Buying Interest - Suryowati, Budi; Nur Mila Chofifah (Universitas Indonesia Membangun (Inaba), 2024)
The number of TikTok users in Indonesia reached 157.6 million users as of July 2024. Important factors in the social media platform include live streaming sales, trust, and content marketing. This study aims to examine how live streaming sales, trust, and content marketing on TikTok affect consumer buying interest. The population in this study is TikTok application users in DKI Jakarta with a sample size of 100 people obtained using the Slovin formula. Sampling was done using purposive sampling techniques. Data analysis using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method with SmartPLS software version 4. The results of the study show that live streaming of sales on the Tik Tok application has an effect on buying interest. Trust has no effect on buying interest on the Tik Tok Application. Marketing Content Affects Buying Interest on the Tik Tok Application